Step-by-step explanation:
We are told to express the given question in standard form,
To do this, we will use the FOIL method
This is method is shown below
In solving the question
![(3x+1)(x-1)](https://img.qammunity.org/2023/formulas/mathematics/college/se5d3l89myyeyxedbzasq1r7aphmygo18i.png)
Applying this, we will have
![\begin{gathered} First=3x* x=3x^2 \\ Outer=3x*-1=-3x \\ \text{Inner}=1* x=x \\ \text{Last}=1*-1=-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/noeqv6ri67a49zys9s4nt5vmmtz8jb7baq.png)
Therefore the standard form will be to combine the terms above and then simplify
![\begin{gathered} =3x^2-3x+x-1 \\ =3x^2-2x-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/jqeax4aagvg55hhgf7utvvg7u27aynk1yo.png)
Therefore, the answer in standard form is
3x²-2x-1